Effect of different herbicides on weed dynamics in green gram under western arid region of Rajasthan - Varsha Jeetarwal; S. P. Singh; Sachin Saini; Rahul (Annals of Agricultural Research, 2025)
A field experiment was carried out at SKRAU Bikaner during kharif, 2022 on loamy sand soil to evaluate the “Effect of the weed management in green gram [Vigna radiata (L.) Wilczek] under Western arid region of Rajasthan”. The experiment was laid out in randomized block design with 10 treatments and 3 replications. The treatments comprised of weedy check, weed free, Pendimethalin 750 g ha-1 PE, Diclosulam 20 g ha-1 PE, Flumioxazin 75 g ha-1 PE, Pendimethalin + Imazethapyr (30+2) 800 g ha-1 PE, Imazethapyr 50 g ha-1 PoE, Quaizalofop + Imazethapyr (7.5+15) 65 g ha-1 PoE, Imazethapyr + Imazamox (35+35) 50 g ha-1 PoE, Sodium acifluorfen + clodinafop (16.5+8) 240 g ha-1 PoE. Among the herbicides, pre emergence application of Pendimethalin + Imazethapyr 800 g ha-1 recorded highest weed control efficiency (92.7%) and weed index (3.36) due to reduction in total weed density (1.71 no. m-2) and weed dry matter (3.35 g m-2).